An Analysis of Phonology, Morphology, and Syntax Acquisition toward a Child in Islamic Review - Reflianto Reflianto; Farida Ariani; Nora Afnita (International Journal on Advanced Science, Education, and Religion, 2018)
The purpose of research is to explore how a baby girl getting the experience of language acquisition in the line of phonology, morphology and syntactic. The research method was descriptive qualitative research by case study design. The subject of research was a baby girl at 2.5 years old. The study took three months was started from September to November 2018 in the village of Koto Pulai, Koto Tangah District of Padang City. Results of the research showed that a baby girl has been able to pronounce some phonemes and words, although still limited to the environmental language and objects are presented nearby her. At the age of 2.5 years old, a baby girl was able to use nouns and verbs and can make simple sentences in the form of declarative, imperative and interrogative sentences involving 2-3 words as a syntax. The process of sounding production when seeing from the Islamic teachings can be understood that each time of a child born out, he or she acquired the language from his or her mother and family. Islam said this process of a baby knowing the surrounding object names as mentioned in Al Quran in verse 31 of Al-Baqara